MRI Changes in Sydenham’s Chorea - J Gordon Millichap (Pediatric Neurology Briefs, 1996)
Cerebral MRIs of 24 children with Sydenham’s chorea and 48 matched controls were compared at the National Institutes of Health, Bethesda, MD.